1988
DOI: 10.1128/aac.32.10.1500
|View full text |Cite
|
Sign up to set email alerts
|

In vitro susceptibilities of mycoplasmas and ureaplasmas to new macrolides and aryl-fluoroquinolones

Abstract: In vitro activities of the new macrolides clarithromycin, previously designated A-56268 , and A-63075 and of the aryl-fluoroquinolones difloxacin (A-56619) and temafloxacin (A-62254) against 14 strains of Mycoplasma pneumoniae, 20 strains of Mycoplasma hominis, and 28 strains of Ureaplasma urealyticum were compared with that of erythromycin. All The number of organisms added was verified by serial tenfold dilutions of the suspension used to inoculate the assay plates (0.1 ml/0.9 ml of broth). These were incu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
32
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(33 citation statements)
references
References 15 publications
0
32
1
Order By: Relevance
“…Some workers have suggested in vitro synergy of clarithromycin and 14-OH-clarithromycin against H. influenzae [3,24), although the relatively low levels of 14-OH in ELF and mucosa in our study may not support this occurrence in vivo. The low MIC 90 (0.03 mg·l -1 ) of clarithromycin against Mycoplasma pneumoniae [25] and against Legionella pneumophila (MIC 90 , 0.12 mg·l -1 ) [26] suggest high efficacy in these atypical pneumonias. Initial clinical studies in severe Legionella pneumophila infection have been favourable [27].…”
Section: Discussionmentioning
confidence: 99%
“…Some workers have suggested in vitro synergy of clarithromycin and 14-OH-clarithromycin against H. influenzae [3,24), although the relatively low levels of 14-OH in ELF and mucosa in our study may not support this occurrence in vivo. The low MIC 90 (0.03 mg·l -1 ) of clarithromycin against Mycoplasma pneumoniae [25] and against Legionella pneumophila (MIC 90 , 0.12 mg·l -1 ) [26] suggest high efficacy in these atypical pneumonias. Initial clinical studies in severe Legionella pneumophila infection have been favourable [27].…”
Section: Discussionmentioning
confidence: 99%
“…Recently the efficacy of new quinolones has been demonstrated in vitro against various respiratory pathogens, including M. pneumoniae (2,4,11). In this report, we compared the in vitro activity of moxifloxacin, a new member of the fluoroquinolone group which has potent antimicrobial activities against grampositive and gram-negative bacteria (3, 9), with those of other fluoroquinolone as references against M. pneumoniae.…”
mentioning
confidence: 99%
“…Quinolones have attracted interest for their use as potential therapy for community-acquired respiratory tract infections because they are active against a wide range of pathogens responsible for these infections, including Mycoplasma pneumoniae and C. pneumoniae (4)(5)(6)(7)(8)(9). We previously reported that ofloxacin, temafloxacin, and sparfloxacin had significant activities against C. pneumoniae in vitro (4).…”
mentioning
confidence: 99%